Efektivitas Sistem Informasi Akuntansi, Pemanfaatan, Kesesuaian Tugas dan Kinerja Karyawan Lembaga Perkreditan Desa - Antari, Ni Wayan Meli; Utama, I Made Karya (E-Jurnal Akuntansi, 2022)
Good employee performance is driven by the effectiveness of accounting information systems, utilization of information technology and suitability of tasks with information technology. The research objective is to provide empirical evidence of the effectiveness of accounting information systems, the use of information technology, and the suitability of tasks with information technology on employee performance. The research was carried out at the Village Credit Institution in Tegallalang. The total respondents used are 110 employees, using purposive sampling technique. Data were analyzed using PLS. The findings show that the effectiveness of accounting information systems, the use of information technology, and the suitability of tasks with information technology have a positive and significant impact on employee performance, meaning that these findings can confirm the TAM theory and the TPC theory. Keywords: Effective Of Accounting Information System; Information Technology Utilization; Suitability Of Tasks;  Employee Performance.